Cardiomyocyte cell cycle dynamics and proliferation revealed through cardiac-specific transgenesis of fluorescent ubiquitinated cell cycle indicator (FUCCI). (February 2019) - Alvarez, Roberto; Wang, Bingyan J.; Quijada, Pearl J.; Avitabile, Daniele; Ho, Thi; Shaitrit, Maya; Chavarria, Monica; Firouzi, Fareheh; Ebeid, David; Monsanto, Megan M.; Navarrete, Natalie; Moshref, Maryam; et al.
Abstract: Rationale: Understanding and manipulating the cardiomyocyte cell cycle has been the focus of decades of research, however the ultimate goal of activating mitotic activity in adult mammalian cardiomyocytes remains elusive and controversial. The relentless pursuit of controlling cardiomyocyte mitosis has been complicated and obfuscated by a multitude of indices used as evidence of cardiomyocyte cell cycle activity that lack clear identification of cardiomyocyte "proliferation" versus cell cycle progression, endoreplication, endomitosis, and even DNA damage. Unambiguous appreciation of the complexity of cardiomyocyte replication that avoids oversimplification and misinterpretation is desperately needed. Objective: Track cardiomyocyte cell cycle activity and authenticate fidelity of proliferation markers as indicators of de novo cardiomyogenesis in post-mitotic cardiomyocytes. Methods and results: Cardiomyocytes expressing the FUCCI construct driven by the α-myosin heavy chain promoter were readily and uniformly detected through the myocardium of transgenic mice. Cardiomyocyte cell cycle activity peaks at postnatal day 2 and rapidly declines thereafter with almost all cardiomyocytes arrested at the G1/S cell cycle transition. Myocardial infarction injury in adult hearts prompts transient small increases in myocytes progressing through cell cycle without concurrent mitotic activity, indicating lack of cardiomyogenesis. In comparison, cardiomyogenic activity during early postnatal development correlated with coincidence of FUCCI and cKit + cells that were undetectable in the adult myocardium. Conclusions: Cardiomyocyte-specific expression ofF luorescenceU biquitination-basedC ellC ycleI ndicators (FUCCI) reveals previously unappreciated aspects of cardiomyocyte cell cycle arrest and biological activity in postnatal development and in response to pathologic damage. Compared to many other methods and model systems, the FUCCI transgenic (FUCCI-Tg) mouse represents a valuable tool to unambiguously track cell cycle and proliferation of the entire cardiomyocyte population in the adult murine heart. FUCCI-Tg provides a desperately needed novel approach in the armamentarium of tools to validate cardiomyocyte proliferative activity that will reveal cell cycle progression, discriminate between cycle progression, DNA replication, and proliferation, and provide important insight for enhancing cardiomyocyte proliferation in the context of adult myocardial tissue.